Experimental investigation on axial compression behavior of steel reinforced concrete columns with welded stirrups. (1st April 2020) - Sun, Lele; Ma, Qijie; Han, Fei; Liu, Zexin; Li, Jinglong; Wang, Peijun; Zhao, Hui; Sun, Jian
Highlights: A novel Steel Reinforced Concrete Column with Welded Stirrups (SRCC-WS) was proposed. Tests on axial compressive behavior of SRCC-WS were carried out. SRCC-WS has higher yield strength and ductility than those of traditional SRCC. A simplified method for calculating concrete confined pressure was proposed. Yield strength obtained by proposed method agreed well with test result. Abstract: Test results on S teel R einforced C oncrete C olumn with W elded S tirrups (SRCC-WS) were presented and a simplified design method was proposed. The SRCC-WS had no longitudinal steel bars to reduce the labor forces and avoid the difficulty in connecting longitudinal bars at construction site, and stirrups were welded directly to the steel reinforcement to ensure they worked together. Five SRCC-WSs were tested under axial compression; and two traditional Steel Reinforced Concrete Columns (SRCCs) were tested for comparison. Failure modes, load-displacement curves, and strain evolution curves measured from tests were presented. Test results showed that the ultimate axial compression strength and ductility of a SRCC-WS was a little higher than that of a SRCC having the same overall steel ratio. A simplified design method for calculating the effective lateral confined pressure on the core concrete provided by the combined action of welded stirrups and steel reinforcement flanges was proposed. The calculated yield compression strength of a SRCC-WS based on the proposed concrete model agreed better with the experimental value than that calculated by the method in Eurocode 4.